Optimizing laboratory production of Strelkovimermis spiculatus (Nematoda: Mermithidae) with a discussion of potential release strategies for mosquito biological control - Achinelly, Maria Fernanda (2011)
Strelkovimermis spiculatus preparasite (J2) infectivity and postparasite (J4) production in rearing pans using a laboratory host, second instar Aedes aegypti mosquitoes. First, we evaluated efficiency of postparasite production by testing increasing J2 concentrations (preparasite:host ratios). Using 10 000 host larvae per rearing pan, we obtained the maximum yield of J4s (3.50 g), number of J4s/larva (3.1), and parasitism frequency (94.9 ± 9.5%) at a 10:1 ratio of J2/larva, although the 10:1 ratio resulted in significantly a male-biased sex ratio. The highest percentage of J2s emerging as J4s was 32% at 1:1 J2s/larva. Second, postparasites were evaluated as an inoculation method using two culture conditions (cultures dessicated or permanently flooded) reflecting two categories of mosquito habitats. The J4´s were allowed to develop to adults, mate, and oviposit in the substrate. The J2s from flooded cultures hatched from eggs at the third week and continued in continuously flooded habitat for up to 30 weeks, with a total J2 production of 6.2 x 10 per rearing pan. Maximum yield of J2s in dessicated cultures occurred on the first flooding (5 weeks), but preparasite emergence continued in subsequent drying-flooding cycles for ten weeks. Total J2 production from intermittently-flooded habitat was 4.5 x 10 per rearing pan. The J2s were always infective for mosquito larvae under both conditions. Either S. spiculatus preparasites or postparasites could be utilized for mosquito biological control in temporary or permanent mosquito habitats, and strategies for this are discussed.